2017
DOI: 10.1159/000479457
|View full text |Cite
|
Sign up to set email alerts
|

C/EBPα Suppresses Lung Adenocarcinoma Cell Invasion and Migration by Inhibiting β-Catenin

Abstract: Background/Aims: The transcription factor CCAAT/enhancer-binding protein α (C/EBPα) is a basic leucine zipper transcription factor that plays essential roles in tumor progression. Although decreased or absent C/EBPα expression in many cancers suggests a possible role for C/EBPα as a tumor suppressor, the functions of C/EBPα in lung adenocarcinoma remain unclear. Methods: Here, C/EBPα expression levels in 26 lung adenocarcinoma and para-carcinoma tissue samples were detected by qRT-PCR and immunohistochemistry.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 32 publications
2
11
0
1
Order By: Relevance
“…In addition, CEBPA-mediated upregulation of PLIN2 promotes chronic myelocytic leukemia progression by -catenin signaling pathways [33]. In lung adenocarcinoma, CEBPA suppresses migration, invasion and EMT of lung adenocarcinoma cells by inhibiting the -catenin [20]. In our study, we found that knockout of CEBPA activated -catenin signaling in ovarian cancer cells, while CEBPA overexpression suppressed -catenin activation.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…In addition, CEBPA-mediated upregulation of PLIN2 promotes chronic myelocytic leukemia progression by -catenin signaling pathways [33]. In lung adenocarcinoma, CEBPA suppresses migration, invasion and EMT of lung adenocarcinoma cells by inhibiting the -catenin [20]. In our study, we found that knockout of CEBPA activated -catenin signaling in ovarian cancer cells, while CEBPA overexpression suppressed -catenin activation.…”
Section: Discussionsupporting
confidence: 54%
“…In breast cancer, CEBPA is required to maintaining epithelial homeostasis by repressing the expression of key mesenchymal markers and preventing EMT [17]. CEBPA is involved in the homeostasis of gastric epithelium [18], and represses migration and/or invasion of cervical squamous cell carcinoma and lung adenocarcinoma [19,20]. In our study, we found that CEBPA knockout facilitated migration, invasion and EMT of ovarian cancer cells, while overexpression of CEBPA exhibited opposite effects.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…It was shown that pioglitazone induced expression of a broad array of PPAR-γ target genes including C/EBPα in mice with paired box gene 8 fusion protein thyroid carcinomas [ 39 ]. Previous researches also reported that C/EBPα can inhibit lung cancer development through the p38α MAPK pathway and suppress lung cancer cell invasion and migration [ 40 , 41 ]. As the results showed, C/EBPα expression was increased and decreased to varying degrees by RGZ or LGZ when co-treatment with TGF-β1, maybe due to different mutational profiles of two thyroid cancer cell-lines [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear β-catenin forms a stable complex with members of the TCF/LEF transcription factor family and induces the expression of target genes such as c-MYC and CCND1 , and influences the metastatic cascade by regulating the expression of genes such as AXIN2 , SNAIL , ZEB1 , COX2 , and S100A4 [ 18 ]. It has been reported that the Wnt/β-catenin signaling pathway is involved in the invasion and metastasis of tumor cells in patients with NSCLC [ 19 , 20 , 21 , 22 ]. In addition to the nuclear translocation of β-catenin by NME1 silencing, Wnt/β-catenin-mediated resistance to cisplatin has been demonstrated in human cancers [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%